Observing System Simulation Experiments for air quality. (August 2015) - Timmermans, R.M.A.; Lahoz, W.A.; Attié, J.-L.; Peuch, V.-H.; Curier, R.L.; Edwards, D.P.; Eskes, H.J.; Builtjes, P.J.H.
Abstract: This review paper provides a framework for the application of the Observing System Simulation Experiment (OSSE) methodology to satellite observations of atmospheric constituents relevant for air quality. The OSSEs are experiments used to determine the potential benefit of future observing systems using an existing monitoring or forecasting system and by this can help to define optimal characteristics of future instruments. To this end observations from future instruments are simulated from a model representing the realistic state of the atmosphere and an instrument simulator. The added value of the new observations is evaluated through assimilation into another model or model version and comparison with the simulated true state and a control run. This paper provides an overview of existing air quality OSSEs focusing on ozone, CO and aerosol. Using illustrative examples from these studies we present the main elements of an air quality OSSE and associated requirements based on evaluation of the existing studies and experience within the meteorological community. The air quality OSSEs performed hitherto provide evidence of their usefulness for evaluation of future observations although most studies published do not meet all the identified requirements. Especially the evaluation of the OSSE set-up requires more attention; the differences between the assimilation model and the simulated truth should approximate differences between models and real observations. Although this evaluation is missing in many studies, it is required to ensure realistic results. Properly executed air quality OSSEs are a valuable and cost effective tool to space agencies and instrument builders when applied at the start of the development stage to ensure future observations provide added value to users of Earth Observation data. Highlights: We provide a framework for the application of OSSEs for air quality issues. We identify the main elements for air quality OSSEs. For each element of these OSSEs, we define a set of requirements. We present illustrative examples from existing air quality OSSEs. We recommend OSSEs for the optimal design of air quality instruments.